(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
Objective: Significant transformations have taken place in the marketing industry over the past century. The extent of the transformation in marketing strategies, tools, and tactics is truly difficult to grasp. In a traditional economy, the market was restricted to a particular physical space, facing constraints concerning time, location, and utility. Globalization has led to a significant contraction of the market, bringing it within the reach of our hands, as all markets are now easily accessible. Initially created as a means for social interaction, social media has evolved into a powerful instrument for brand positioning, advertising, and various other aspects of marketing management. Staying informed about the most recent developments in the marketing and tooling sectors is essential for any organization. The main objectives of the paper are to enhance readers’ knowledge and to improve their understanding of social media marketing. This study provides a bibliometric analysis of social media marketing research spanning from 2009 to 2024 to assist scholars in the field.Approach/Methodology/Design: The Scopus database was employed to examine how research in social media marketing has developed over the years, to find out the leading authors, countries, documents and journals in this research domain, to study the keyword occurrence pattern in the field of social media marketing and to investigate the association between the citations and co-citations of social media marketing research articles.Results: It has been noted that the researches in social media marketing were minimal till 2014, gaining momentum after 2015 and peaking in 2024. Ko, Eunju is found to be most impactful author whereas Dwivedi, Yogesh K. is most productive author. The country that has significantly influenced the realm of social media marketing is United States. Most prominent article is Kozinets titled “Networked narratives: Understanding word-of-mouth marketing in online communities” and the most impactful journal in this field is “Journal of Business Research”.